Produção de etanol a partir de xilose com glicose isomerase e Saccharomyces cerevisiae coimobilizadas em gel de alginato - Aquino, Patrícia Marina de (2013)
In this work, it was studied the simultaneous isomerization and fermentation of xylose to ethanol (SIF) using xylose isomerase (XI) and S. cerevisiae co-immobilized in calcium alginate gel. XI was immobilized on chitosan gel activated with glutaraldehyde (IXI-Ch). The influence of the concentration of enzyme/yeast in the reactor, the pH, temperature and yeast strain on yield and selectivity in ethanol was studied. The concentrations of enzyme and yeast in the reactor were varied by changing the mass of IXI-Ch and yeast per gram of alginate solution, maintaining fixed the ratios of biocatalyst weight: volume of medium in the reactor (1:1). The SIFs were carried out in batch with xylose (65g.L-1), antibiotics and other salts. The first experiment, with 16% Itaiquara® yeast and 5% enzyme biocatalyst (% wenzyme or yeast/wbiocatalyst) showed that pH drop occurred during the test, preventing full conversion of xylose, due to reduced enzyme activity. calcium carbonate (0.5-1.0%) was then included in the biocatalyst, which maintained the pH between 5,2 to 5,6, allowing complete conversion of the sugar at all concentrations tested (%Yeast -Enzyme in biocatalyst): 5-20, 17-5, and 10 yeast (Itaiquara ®) with 5, 10 and 20-. The maximum ethanol productivity, 2,44 ± 0,26g.L-1.h- 1 was obtained for the highest cell concentration and the highest selectivity ethanol/xylitol, 2,57 ± 0.4 and 2,42 ± 0,01 for the highest enzyme concentrations (10 and 20% with 10% yeast). These results indicated that the highest concentration of xylulose favored more selectivity to ethanol. Fermentation was then performed using no enzyme in biocatalyst with a prior isomerized syrup concentrated in xylulose containing 58g.L-1 xylulose and 9g.L-1 xylose and another with xylose only. At first, xylulose was completely assimilated in 5 hours, xylose was barely consumed in both assays, and ethanol selectivity was lower than that obtained in the SIF tests. Xylitol show thus to be produced mainly from xylulose and selectivity contrary to expectations did not directly increase with increasing xylulose concentration, indicating that the formation of ethanol/xylitol depends not only on external xylulose, and it is probably finely regulated in yeast. The concentrations of enzyme and yeast 20 and 10% (equivalent to 100gderived.L-1 reactor and 50gwd.L-1 reactor) were selected as the best, which were used to study the influence of pH and temperature, and also different strains. The increase of initial pH from 5.6 to 6.5 did not improve the productivity, yield, neither selectivity in ethanol. Temperatures tested for Itaiquara ® were 32, 35 and 37 ° C, and for industrial strains CAT-1 and BG-1: 32, 37 and 40 ° C. Viability remained above 90% for all assays at 24 hours. All three strains showed increased selectivity in ethanol with temperature reduction, obtaining the maximum selectivity for industrial strains (3,06 ± 0,24 - CAT-1 and 3,19 ± 0,11 BG-1) with yield and productivity equal or greater than those obtained in higher temperatures. At 32 ° C and pH 5.6, Itaiquara ® showed lower conversion time, but lower selectivity, while the BG-1, demonstrated the highest selectivity, but low conversion and productivity. The strain CAT-1 combines high productivity, 2,17 ± 0,17 g.L-1.h-1, and selectivity, 3,06 ± 0,24, with 90% conversion in 9 hours, 32 ° C, which is apparently the best performance among the tested yeasts. The results were very promising, indicating the technical feasibility of producing ethanol from xylose with the biocatalyst developed.